Persulfate-Enabled Direct C–H Alkylation of Heteroarenes with Unactivated Ethers - McCallum, Terry; Jouanno, Laurie-Anne; Cannillo, Alexandre; Barriault, Louis (Synlett, 2016)
Protocol simplification is an important aspect in the development of organic reactions such as heteroarene functionalizations. An operationally facile protocol for the direct C–H alkylation of heteroarenes with unactivated ethers has been developed. The Minisci-type radical addition process involves thermolysis of potassium persulfate, circumventing the need for transition-metal catalysts.
Keywords: heterocycles; C–H functionalization; Minisci reaction; persulfates; ethers